Training progression from junior to senior levels in biathlon - Kock, H. (Journal of Biathlon Coaching, 2025)
Biathletes undergo extensive physical and shooting training to meet the unique demands of their sport. Their training emphasizes endurance at mostly low intensities, supported by strength and speed work, combined with large volumes of shooting practice performed both at rest and under physical stress. Training methods vary by individual and evolve as athletes progress from junior to senior levels, reflecting growing specialization and the increasing pace and complexity of competition. Understanding these training characteristics is essential to optimizing long-term development and performance in biathlon.